Penghitungan Kapasitas Volume Tampungan Embung Rogodadi Kabupaten Kebumen - Indra Suharyanto; Singgih Subagyo (CivETech, 2022)
Rogodadi is a village in the sub-district of Buayan, Kebumen, Central Java, Indonesia. This village is around 2.2 kilometers from the center of Buayan sub-district and 28 kilometers from the capital of Kebumen Regency through Kuwarasan. Rogodadi has a location that has the potential to be developed into a reservoir. The purpose of this study was to determine the optimal storage capacity of the reservoir. Based on Surat Edaran Nomor: 07/SE/M/2018 tentang Pedoman Pembangunan Embung Kecil Dan Bangunan Penampung Air Lainnya Di Desa, the capacity of the reservoir is carried out by taking into account water needs, water availability and topography. After calculating, it is found that the storage capacity based on water needs (Vn) is 21.033,74 m3. Based on the analysis of water availability (potential) during the rainy season (Vh), the volume of water that can be accommodated is 22.869,00 m3. The design capacity of a reservoir (Vd), which is equal to Vd = 21.000 m3 with height of dam 3.00 m.